A COMPARATIVE STUDY REGARDING THE LEARNING STYLES OF TURKISH UNDERGRADUATE GEOGRAPHY STUDENTS AND THEIR WESTERN COUNTERPARTS - Özdemir, Nevin (Fırat University, 2015)
It has been argued that culture has a significant impact on learning styles. Turkey is one of the nonWestern countries according to studies on the classification of countries based on cultural characteristics. Therefore, the primary objective of this study was to compare the learning styles of geography undergraduates in Turkey with the findings of a previous international study in which the learning styles of Western geography undergraduates were assessed. Kolb’s Learning Styles Inventory was used as a measurement tool in order to facilitate this comparison, and 1275 Turkish geography undergraduates studying at eight universities in different geographical regions of Turkey responded to this inventory. The data obtained from the study were analyzed to compare the learning styles with those of Western geography undergraduates. According to the research findings, the assimilating and converging learning styles were favored between Turkish geography undergraduates, while the assimilating learning style was favored between Western geography undergraduates. Similar to Western counterparts, there are significant differences between demographic variables such as age and class of and predominant learning styles of Turkish geography undergraduates within 10 departments.